Engineered phage with antibacterial CRISPR–Cas selectively reduce E. coli burden in mice - Gencay, Yilmaz Emre; Jasinskytė, Džiuginta; Robert, Camille; Semsey, Szabolcs; Martínez, Virginia; Petersen, Anders Østergaard; Brunner, Katja; de Santiago Torio, Ana; Salazar, Alex; Turcu, Iszabela Cristiana; Eriksen, Melissa Kviesgaard; Koval, Lev; et al. (Nature biotechnology, 2024)
Antibiotic treatments have detrimental effects on the microbiome and lead to antibiotic resistance. To develop a phage therapy against a diverse range of clinically relevant Escherichia coli , we screened a library of 162 wild-type (WT) phages, identifying eight phages with broad coverage of E. coli , complementary binding to bacterial surface receptors, and the capability to stably carry inserted cargo. Selected phages were engineered with tail fibers and CRISPR–Cas machinery to specifically target E. coli . We show that engineered phages target bacteria in biofilms, reduce the emergence of phage-tolerant E. coli and out-compete their ancestral WT phages in coculture experiments. A combination of the four most complementary bacteriophages, called SNIPR001, is well tolerated in both mouse models and minipigs and reduces E. coli load in the mouse gut better than its constituent components separately. SNIPR001 is in clinical development to selectively kill E. coli , which may cause fatal infections in hematological cancer patients. Phage engineered with tail fibers and CRISPR–Cas reduce Escherichia coli load in animals.